Distributed scheduling approach for dynamic evacuation networks. Issue 6 (2nd November 2017) - Saeed Osman, Mojahid; Ram, Bala
ABSTRACT: The aim of this paper is to propose a novel distributed scheduling model for evacuation route scheduling from buildings and out of an affected area. The model is based on a hybrid approach that is spatio-temporal algorithm with optimization models as subproblems. The proposed distributed scheduling approach is an iterative process optimizing the one-step arrival of objects to each intermediate destination nodes at a time. To illustrate such an approach, we consider the problem of finding and scheduling evacuation paths from an urban building and out of a predetermined neighbourhood of the building on foot; the evacuation route involves pathways such as corridors, and stairs in buildings and road networks and sidewalks outside the building, there is a predefined set of exit points out of the target building and out of the road network serving the building. A well-known efficient heuristic algorithm is selected as a reference for comparative analysis and to illustrate the outperformance of the proposed approach in large-scale scenarios. The key results are the step-based optimal route schedules and the competitive evacuation time provided by the proposed distributed scheduling approach.